Analisis Library Anxiety terhadap Mahasiswa di Perpustakaan Fakultas Bahasa dan Seni Universitas Negeri Padang - Hafizhah, Riyana; Erlianti, Gustina (Lembaga Yasin AlSys, 2024)
This research aims to describe how library anxiety is experienced by students and what factors cause library anxiety in students entering 2023 at the Library of the Faculty of Languages and Arts, Padang State University using the library anxiety indicator Swigon (2011). This research is qualitative research using the phenemonological method. Determining informants in this research was carried out using a purposive sampling technique. Data collection was carried out using interview and observation methods. Data validation was carried out by triangulating sources and time and analyzed through data reduction, data presentation and drawing conclusions. The results of this research show that: (1) the frequency and purpose of students visiting the FBS library is based on different reasons, such as students feeling that the library does not provide the information they need, crowded library conditions sometimes make students afraid to go to the library alone, libraries that often crowded means students don't get any more seats, and library regulations that don't suit students' learning styles; (2) barriers with staff describes a situation where students feel that FBS library staff are intimidating figure; (3) affective barriers which give feelings of fear, awkwardness and discomfort become obstacles when students have to deal with the FBS library; (4) technological barriers where this is not an obstacle for students when using the FBS library because of the ease that students feel when using technology; (5) library knowledge barriers that arise due to students' lack of knowledge of libraries which makes them feel lazy about visiting the FBS library; (6) library comfort barriers are characterized by feelings of discomfort experienced by students while in the FBS library; (7) resource barriers experienced by students where students feel there is still a lack of availability and diversity of collections available in the FBS library.